2012
DOI: 10.3945/jn.111.145516
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Acculturation Status Are Associated with Dietary Intake and Body Weight in Mexican American Adolescents,

Abstract: Mexican American children are disproportionately affected by obesity. Data on how the acculturation process influences diet and body weight among adolescents are limited. We used the data from the 1999-2004 NHANES, restricting to 2286 Mexican American children between 12 and 19 y old. Acculturation was measured by generation status and language preference. Diet was assessed using 24-h diet recall. Multiple linear, Tobit, logistic, and quantile regression models were used. We found, after adjusting for socio-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
86
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 38 publications
5
86
0
1
Order By: Relevance
“…The young age of the children (2-8 years) in our study may explain why no effect of acculturation on vegetable intake was observed. Similar to our findings, other research shows that parenting practices, such as positive role modelling, may partially mitigate negative influences of acculturation on access and availability of fruit and vegetables in Latino households with children (39) .…”
Section: Discussionsupporting
confidence: 91%
“…The young age of the children (2-8 years) in our study may explain why no effect of acculturation on vegetable intake was observed. Similar to our findings, other research shows that parenting practices, such as positive role modelling, may partially mitigate negative influences of acculturation on access and availability of fruit and vegetables in Latino households with children (39) .…”
Section: Discussionsupporting
confidence: 91%
“…13 Research has revealed the importance of generational status and acculturation of the adolescent and family on nutritional intake, quality of food choices, food preparation, obesity status, and food insecurity. [14][15][16][17] However, to our knowledge, no published study has captured adolescents' navigation through these unique cultural and developmental struggles in their own words.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for providers include incorporating knowledge of adolescent development and culturally sensitive care into treatment recommendations. 17.4% of Mexican-American females. 1 The medical consequences of childhood and adolescent obesity are well documented, with increased morbidity and mortality rates and impaired quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct consumption patterns were observed across racial/ethnic subpopulations; for example, non-Hispanic Asians obtained a greater percentage of fruit from citrus fruits compared to non-Hispanic white youth. Variations in the types of fruits consumed by race and Hispanic origin may be related to acculturalization, 24,25 accessibility, and social experiences. 23 We found that over half of all fruit consumed by youth aged 2-19 y is whole fruit (52.9%) and another third is consumed as 100% fruit juice (33.5%).…”
Section: Discussionmentioning
confidence: 99%